One-step removal of Cr(VI) at alkaline pH by UV/sulfite process: Reduction to Cr(III) and in situ Cr(III) precipitation - Xie, Bihuang; Shan, Chao; Xu, Zhe; Li, Xuchun; Zhang, Xiaolin; Chen, Jiajia; Pan, Bingcai (Chemical engineering journal (Lausanne, Switzerland : 1996), 2017)
[Display omitted] •Cr(VI) was efficiently reduced to Cr(III) at alkaline pHs by UV/sulfite process.•Common ions and organic matters interfered with Cr(VI) reduction slightly.•Spontaneous precipitation of Cr(III) occurred in the presence of Ca2+ (>2ppm).•eaq− was identified as the dominant reactive species in UV/sulfite process. Chemical reduction of Cr(VI) to Cr(III) followed by Cr(III) precipitation is a widely employed strategy to mitigate Cr(VI) pollution from industrial effluents. Nevertheless, most of the available reduction processes are feasible at acidic pHs only, and very few technologies are capable of reducing Cr(VI) at alkaline pHs. Herein, we demonstrated that the UV/sulfite process is very promising for alkaline Cr(VI) remediation, including the Cr(VI) reduction to Cr(III) and simultaneous Cr(III) precipitation. In this process Cr(VI) reduction followed near zero-order kinetics, declining with an increase of pH (5–10) but boosting with increasing sulfite concentration. The co-existing Cl− and SO42− in water exerted negligible effect on Cr(VI) reduction, whereas the reduction kinetics was improved in the presence of citrate, EDTA or humic acid possibly due to their complexation with Cr(III). Similarly, the presence of borate buffer would significantly inhibit Cr(VI) reduction to Cr(III) as well as the final Cr(III) removal during precipitation. Fortunately, the presence of calcium ions even at trace level would favor Cr(III) precipitation and result in one-step removal of the total Cr at alkaline pH. The mechanism of Cr(VI) reduction was probed through irradiation manipulation and N2O addition, and the results suggested that excitation of sulfite is essential for alkaline Cr(VI) reduction, and eaq− is the dominant reactive species in the UV/sulfite process.